Determinants of late ante-natal care booking among pregnant women in Marondera district, Mashonaland East, Zimbabwe. - Muchenje, Davison; T. Zizhou, Dr. Simukai; Chitura, Miriam (IJRDO - Journal of Social Science and Humanities Research, 2016)
Maternal mortality remains a huge public health problem in developing countries. Antenatal care (ANC) is one of the key strategies to improve maternal health, aiming to promote the wellbeing of the mother and fetus. ANC services utilization is influenced by several factors that vary from one community to another. The study sought to determine factors associated with late ANC booking among pregnant women in Marondera district in Zimbabwe. A 1:1 unmatched case control study was conducted among 180 pregnant women at 6 health facilities in Marondera district in Zimbabwe. Structured questionnaires were used to obtain information from study participants. Epi Info 7 software was used to generate frequencies, draw graphs, calculate odds ratios, and confidence intervals. Logistic regression analysis was used to identify variables associated with late ANC visits. At least 80% of both cases and controls were aware of most benefits of registering for ANC. 66.7% of cases and 98.9% of controls were aware that booking is done during 0-16 weeks of pregnancy. More than half of the participants were aware that pregnant women are expected to complete at least 4 ANC visits. Waiting for permission from others to access ANC (AOR 9.74 95% CI 1.92-49.34) and perceiving self as at low risk of developing complications (AOR 3.29 95% CI 1.67-6.49) were independent risk factors associated with late ANC booking. Receiving motivation from spouse (AOR 0.24 95% CI 0.12- 0.48) and receiving motivation from health workers (OR 0.38 95% CI 0.19-0.77) was associated with a less likelihood to book late for ANC. Having attended previous antenatal care clinic (OR 0.51 95% CI 0.23-1.09) was associated with a less likelihood to book late for ANC by pregnant women in Marondera district. Majority of participants knew the importance of ANC. Late ANC booking among pregnant women in Marondera district has been shown to be influenced by waiting for permission from others to access ANC and perceiving self as at low risk of developing complications. Health education aimed at promoting uptake of ANC services should be intensified in the district to ultimately improve maternal and infant health.